Weather Information for Garden City - J. Elliott (Kansas Agricultural Experiment Station Research Reports, 2015)
Garden City, Kansas: Precipitation for 2014 totaled 23.29 in. This was 4.05 in. above the 30-year average of 19.24 in. This was the first year since 2009 with above-normal precipitation and the highest level since 24.69 in. in 2004.
Keywords: weather; rain; snowfall; temperatures